Knowledge, attitudes, and practices of radiology practitioners in Saudi Arabia toward the use of gonad shields during fluoroscopy-guided interventional radiography - Alenezi, Mamdouh S.; Alshammari, Abdulaziz M.; Hassib, Mazin B. (Frontiers in Medicine, 2025)
BackgroundThe utilization of gonad shields in interventional radiology (IR) settings plays a pivotal role in minimizing radiation risk for practitioners.PurposeThis study aims to assess the impact of experience, practitioners’ opinion, education in radiation protection, practitioners’ gender, workload, and educational level on the use of gonad shields.MethodsThis cross-sectional questionnaire study comprised six hypotheses that were designed to fulfill the study’s aim. Normality was assessed using skewness and kurtosis values within a specified threshold. Categorical variables were assessed using cross-tabulation and the chi-square (χ2) test of independence. A p-value of <0.05 was considered statistically significant.ResultsThe study included 527 participants (307 female and 220 male). There was a significant inverse association between years of experience and the frequency of gonad shield use (p < 0.05). A direct relationship was observed between practitioners’ opinions on the importance of gonad shields and shield usage frequency (p < 0.05). It was clear that attending radiation protection training was more likely to encourage practitioners to follow gonad shielding protocols (p < 0.05). No significant effect of gender and gonad shield usage was observed (p = 0.086). Practitioners with higher annual caseloads (>200 cases/year) reported more consistent use of gonad shields (p < 0.05).ConclusionPractice length, but not workload, is inversely related to IR staff’s attitude toward gonad shield use. Continuous radiation protection training is crucial for improving IR staff commitment to safety standards. No impact of gender on gonad shield usage was observed. Targeted refresher training, reinforcement of local guidance, and ensuring shield availability/workflow integration may strengthen occupational radiation-safety adherence in IR units.